Effect of Locality of Growth and Fibre Characteristics of Leucaena leucocephala on Kraft Pulp - Singh, S. V.; Lal, Krishan; Bhandari, S. S.; Singh, S. P. (Indian Forester, 1986)
The paper gives a comparative account of the evaluatinn of Su-babul (L leucocpphala) ,grown in Pune. At Siliguri and Rajabhatkhawa, for bleached grade kraft pulp. The data on pulping and bleaching properties indicate that the wood from all the three sources can be pulped to obtain bleachable grade pulp (Kappa No 26 Â± t) using 17% active alkali as Na2O. The bleached pilip yield was about 45% in an the three cases. To achieve a pulp of 7% brightness CEH sequence with total chlorine application of 9.7% was adequate for samples for Pune and Rajabhatkhawa; whereas in case of Siliguri sample another stage of hypochlorite (2% av. Chlorine) was needed. The strength properties data indicate that wood of all the three localities is suitable for producing bleached kraft pulps for writing and printing papers. It was found that fibre characteristics (The Runkel ratio and shape factor) had marked influence on strenglh properties. The tensile index, tear index and burst index decreased with increase in the hunkel ratio and shape factor.